Teleology of Economic Law: A Comparative Analysis of The Concepts of Material Welfare and Falah - Saputro, Triyono Adi; Rahmawati, Awalia Rina; Saputro, Ramadhan Zuhdi; Safly, Afiq; Fajri, Iskam Auliya (Suhuf: International Journal of Islamic Studies, 2026)
Background: The teleology of economic law reflects core values guiding human economic behaviour within legal systems. Positive law adopts a utilitarian paradigm emphasising material welfare through market stability, property protection, and contract certainty, while Sharia economic law introduces a holistic framework via falah and itmi’nan rooted in maqasid al-shariʿah. This divergence creates implementation tensions in Indonesia’s pluralistic legal system. Objective: This study aims to critically analyse the teleological concept of material welfare in positive economic law and contrast it with the vision of falah in Sharia economic law, identifying convergences, divergences, and integration opportunities. Methodology: Employing normative legal research with a comparative doctrinal approach, this library based study synthesizes primary legal sources and secondary data selected through criterion-based purposive sampling. Results: Positive law prioritises procedural efficiency and material metrics, while Sharia economic law emphasises distributive justice and spiritual well-being. Both systems share commitments to economic order and fraud prevention, yet diverge in their treatment of spiritual versus material priorities, producing suboptimal hybrid policies in sectors such as Islamic finance. Conclusion: Harmonizing positive law’s legal certainty with falah’s ethics produces resilient, non-dualistic models that advance ethical governance in diverse societies. Theoretically, this study enriches comparative legal discourse. Practically, it guides policymakers toward Sharia aligned reforms fostering inclusive growth, and encourages development of maqasid based indices for sustainable development.